Концептуально-правові засади застосування санітарних та фітосанітарних заходів у сільському господарстві України в контексті вимог СОТ та ЄС - Карпінська, Наталія Володимирівна (Одеса, 2021)
Дисертацію присвячено комплексному та всебічному дослідженню концептуально-правових засад застосування санітарних та фітосанітарних заходів у сільському господарстві в Україні в контексті вимог СОТ та ЄС. Робота містить теоретичне узагальнення і нове вирішення наукової проблеми у сфері формування концептуального бачення правового регулювання відносин застосування санітарних та фітосанітарних заходів у сільському господарстві з огляду на міжнародно-правові зобов’язання України.

Досліджуються питання юридичної природи відносин застосування санітарних та фітосанітарних заходів у сільському господарстві, визначаються етапи розвитку законодавства у цій сфері. Аналізуються методологічні проблеми застосування в Україні вимог СОТ та ЄС, а також принципи застосування санітарних та фітосанітарних заходів у сільському господарстві за правом СОТ та ЄС. Приділено значну увагу інституційно-функціональному забезпеченню застосування санітарних та фітосанітарних заходів у сільському господарстві у контексті правових вимог СОТ та ЄС. Досліджено концептуальні основи правового регулювання застосування санітарних та фітосанітарних заходів у рослинництві, тваринництві та при виробництві харчових продуктів.

The dissertation is devoted to a complex and comprehensive study of the conceptual and legal framework for the application of sanitary and phytosanitary measures in agriculture in Ukraine in the context of WTO and EU requirements. The work contains a theoretical generalization and a new solution to the scientific problem in the field of forming a conceptual vision of the legal regulation of the application of sanitary and phytosanitary measures in agriculture in view of Ukraine’s international legal obligations.

The issues of legal nature of relations of application of sanitary and phytosanitary measures in agriculture are investigated, stages of development of the legislation in this sphere are defined. The methodological problems of application of WTO and EU requirements in Ukraine, as well as the principles of application of sanitary and phytosanitary measures in agriculture under WTO and EU law are analyzed.

The author identifies and characterizes the periods of development of agricultural legislation: 1) the stage of formation (1991 – 2004), the characteristic features of which were: a) development of basic laws in reverse order – «from special to general»; b) »schematism» of the first editions of laws; c) involvement in international legal regulation; d) the emergence of European integration; 2) stage of preparation of Ukraine’s accession to the WTO and harmonization with its requirements in the field of sanitary and phytosanitary measures application (2005 – 2013), the main features of which were: a) active reform of laws; b) introduction into the legislation of provisions on the use of the HACCP system; c) adoption of program documents; d) strengthening of normative actions of European integration character; e) further involvement in international legal regulation; 3) the stage of harmonization with the EU legislation (2014 – hitherto) has the following characteristics: a) planning of rule-making activities in accordance with the implementation of the Association Agreement; b) a rapid unsystematic increase in the regulatory framework; c) rule-making is subject to EU legislation; d) detailing of regulatory requirements, their significant specialization; e) implementation of WTO requirements in the field of SPS application is combined with the need to comply with the terms of the Association Agreement.

Considerable attention is paid to the institutional and functional support of the application of sanitary and phytosanitary measures in agriculture in the context of the legal requirements of the WTO and the EU. The conceptual bases of legal regulation of application of sanitary and phytosanitary measures in plant growing, animal husbandry and in food production are investigated.

The author argues that under the influence of globalization and European integration processes, as well as due to the strengthening of environmental trends, modern Ukrainian legislation in the field of SPF is actively transformed, combining three legal entities: phytosanitary legislation, animal welfare legislation and food legislation.

The author substantiates three conceptual ways of development of Ukrainian legislation in the field of SPS: 1) WTO-oriented, is aimed at maximum international unification of legal requirements (positive features: trade facilitation, construction of legislation according to international standards; negative features: dominance of developed countries); 2) EU-oriented, is aimed at maximum approximation to EU legislation (positive features: constant legal progress and greening of agricultural activities; negative features: a) ignoring legal evolutionary gaps, b) lack of appropriate adaptive periods, c) ignoring national characteristics and problems, d) waiver of a significant part of legal sovereignty in this area); 3) national-oriented, is the choice of national interests of Ukraine and the interests of its population – as guidelines and benchmarks for the construction of domestic legislation (positive features: a) directions, pace and scope of reforming legislation meet the level of development and strategic goals of agriculture in Ukraine; b) approximation of legislation to foreign models is primarily through the prism of the use of principles and methodological approaches, rather than through mechanical copying of foreign law; negative – lack of conceptual vision)
Карпінська Н. В. Концептуально-правові засади застосування санітарних та фітосанітарних заходів у сільському господарстві України в контексті вимог СОТ та ЄС. – Рукопис. Дисертація на здобуття наукового ступеня доктора юридичних наук за спеціальністю 12.00.06 – земельне право; аграрне право; екологічне право; природоресурсне право. – Національний університет «Одеська юридична академія», Одеса, 2021.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; санитарные и фитосанитарные меры; сельское хозяйство; право ВТО; право ЕС; аграрное право; sanitary and phytosanitary measures; agriculture; WTO law; EU law; agrarian law